Determinants of phosphorus balance and use efficiency in diverse dairy farming systems. (December 2021) - Harrison, B.P.; Dorigo, M.; Reynolds, C.K.; Sinclair, L.A.; Dijkstra, J.; Ray, P.P.
Abstract: CONTEXT: Identifying the determinants of phosphorus (P) balance and use efficiency (PUE) is critical to improving the sustainability of dairy farming in countries operating diverse dairy farming systems because each system contributes to eutrophication through different pathways. However, information about P balance and PUE across diverse dairy farming systems is scarce. OBJECTIVE: The current study aimed to use a novel approach to determine P balance and PUE, and identify their key determinants across diverse dairy farming systems in GB. METHODS: Data from 29 dairy farms representing systems with differing feeding approaches and production levels was collected from farm records or generated by quantifying P concentration in feed, manure, and soil samples. The methodology of the nutrient management tool 'Planning for Land Application of Nutrients for Efficiency and the environmenT (PLANET) and the principles of 'Annual Nutrient Cycling Assessment' (ANCA) were used to calculate farm-gate P balance (FPB) and soil-surface P balance (SPB), respectively. Differences in P balance and PUE between dairy farming systems were investigated using ANOVA. Determinants of P balance and PUE were identified using multiple stepwise linear regressions. RESULTS AND CONCLUSIONS: The current study demonstrated a novel approach of calculating FPB and SPB that captures differences in the P concentration of manure and milk between systems. Phosphorus surplus was higher and PUE was lower in housed systems compared to pasture-based systems (except for a Spring-calving system grazing ≥274 days/year) primarily because of greater import of concentrate feed, highlighting the importance of reducing concentrate feed import into housed systems to minimise P import. Farms with greater inclusion rate of home-grown feed (primarily forages) in their herds' diet had higher PUE and lower P surplus. Thus, pasture-based systems could improve PUE by increasing the inclusion rate of home-grown feeds in the herd diet only if they maintain a stocking rate that matches the feed demand of the herd to the availability of home-grown feeds. In conclusion, the assessment of PUE and strategies to improve it should consider system classification beyond strict housed and pasture-based systems. SIGNIFICANCE: The current study demonstrated the foundations of an approach to calculate FPB and SPB that could be more robust compared to using standard P coefficients particularly in countries that operate diverse dairy farming systems. With further development, this approach could be adopted and could change the way GB dairy farmers and advisers calculate P balances in diverse systems. Graphical abstract: Unlabelled Image Highlights: Data on P management more specific than housed and pasture-based systems is needed to make dairy farming more sustainable. This study assessed differences in P balances and use efficiency in a diverse dairy farming system using a novel approach. All systems had large P surpluses but farms operating a blended pasture-based farming system were the most P efficient. Strategies to improve P use efficiency should consider system classification beyond strict housed and pasture-based systems. Our P balance estimation approach could inform strategies to improve P use efficiency across diverse dairy farming systems.